EXPERIMENTAL STUDY WITH DIFFERENT STRATEGIES AND AIR-DILUTION USING OPTICAL SI ENGINE FUELED WITH HYDRATED ETHANOL - Silva, M. F.; Lacava, P. T.; Penaranda, A.; Sbampato, M. E.; L. R. Santos, L. R. (Revista de Engenharia Térmica, 2023)
Several dilution conditions techniques are used in internal combustion engines to increase fuel economy and reduce pollutant emissions, primarily nitrogen oxide (NOX), which are generated by the thermal pathway. Among the techniques, we can highlight air dilution (lean combustion) and exhaust gas recirculation (EGR). The control of these operations using different types of fuels and biofuels and their peculiarities, are of fundamental importance to remove the maximum efficiency from the process, generating the lowest level of emission and respecting the current legislation. Although several studies have achieved interesting results for reducing emissions and knocks thanks to the dilution of the air, it has been observed that the diluent without oxygen is more efficient. Although air dilution has a slightly lesser effect than EGR, this mode of operation can help to understand the dynamics of engine load dilution, mainly due to the complexity of EGR tests on research engines. Therefore, as a background, tests were carried out experimentally with air dilution in order to understand the behavior for the prediction of future tests with EGR. The tests were performed with hydrated ethanol and speeds of 1500 rpm and 2500 rpm. It was possible to observe that with increasing dilution, there is a gradual increase in the variability of the burn and its displacement to the region close to the inlet valve. It was observed that the dilution provided a decrease in the formation of NOX and CO and an increase in hydrocarbon emissions. Increased rotation due to increased turbulence causes changes in emission values.